Environmental & architectural phenomenology. Vol. 26, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2015)
Vol. 26, no. 3, fall 2015 (includes “items of interest,” “citations received,” and essays by R. M. Sovich & John Cameron).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals